2015
DOI: 10.1002/app.41941
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nylon 6,6 nanofibers functionalized with cyclodextrins for removal of toluene vapor

Abstract: Functional nylon 6,6 nanofibers incorporating cyclodextrins (CD) were developed via electrospinning. Enhanced thermal stability of the nylon 6,6/CD nanofibers was observed due to interaction between CD and nylon 6,6. X-ray photoelectron spectroscopy and attenuated total reflectance Fourier transform infrared spectroscopy studies indicated the existence of some CD molecules on the surface of the nanofibers. Electrospun nylon 6,6 nanofibers without having CD were ineffective for entrapment of toluene vapor from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 88 publications
3
15
0
2
Order By: Relevance
“…The modeling studies for formation of an inclusion complex between CD and toluene were also performed by using ab initio techniques and the results confirmed that based on the first principles calculation, the complexation energy of toluene-CD is higher for β-CD compared to α-CD and γ-CD as illustrated in Fig. 6.19b [75].…”
Section: Removal Of Volatile Organic Compounds (Vocs)supporting
confidence: 57%
“…The modeling studies for formation of an inclusion complex between CD and toluene were also performed by using ab initio techniques and the results confirmed that based on the first principles calculation, the complexation energy of toluene-CD is higher for β-CD compared to α-CD and γ-CD as illustrated in Fig. 6.19b [75].…”
Section: Removal Of Volatile Organic Compounds (Vocs)supporting
confidence: 57%
“…Hence, they have been heavily used in pharmacy, agriculture, textile, catalysis, hygiene, cosmetic and food industry [30][31][32][33]. Further, in our recent studies we have shown that electrospun nanofibers can be functionalized with cyclodextrins as molecular filters for water filtration [34,35] removal of volatile organic compounds (VOCs) [36][37][38][39][40] including aniline, benzene, styrene and toluene, and the removal of phenanthrene from an aqueous system [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…S10b, ESI †) also supported the findings about the higher loading by the impregnation method. The TGA results showed that Nylon 6,6-NF starts to decompose at around 400 1C 41 and this ends at 510 1C, losing almost all of its components (97%), but when it is decorated with Si QD-90, due to the water and other volatile components, the structures gave three different decomposition regions. First, the impregnated and dip-coated samples appear to have the same decomposition characteristics, but due to the different amount of decoration, the weight% loss amounts are different.…”
Section: Resultsmentioning
confidence: 99%